Development of Computer Vision Algorithms for Multi-class Waste Segregation and Their Analysis - Neeraja Narayanswamy; A. R. Abdul Rajak; Shazia Hasan (Ital Publication, 2022)
Classification of waste for recycling has been a focal point for scientists interested in the field of conservation of the environment. Recycling consists of numerous steps, of which one of the most crucial is the segregation of recyclables from all other waste. Due to a lack of safety standards in developing countries, waste collection is often done manually by domestic helpers, or